Analisis Dampak Penambangan Pasir Terhadap Kesejahteraan Masyarakat Di Kecamatan Pronojiwo Kabupaten Lumajang Menurut Perspektif Islam - Nuronia, Khoviva; Khalikussabir, Khalikussabir; Mahardani, Ahmad Subhan (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this research is to determine the analysis of the impact of sand mining on the welfare of the community in Pronojiwo sub-district, Lumajang district according to Islamic perspectives. Sand mining in Pronojiwo District is very productive in stabilizing the economy of the Pronojiwo community, however it has not been studied regarding the level of sensitivity of entrepreneurs and miners to the halal level of the way it is obtained or the mining process is considered haram in Islam so the income obtained is automatically haram. So with this we will review Islamic law and more specifically the sharia view of how sharia economic law views mining businesses in Pronojiwo District. The method used in this research uses a qualitative descriptive analysis approach. The type of data in this research is qualitative data. Meanwhile, data sources consist of primary and secondary data. Data collection was carried out by means of observation, interviews and documents. The results of this research are that the impact of sand mining in Pronojiwo District has many benefits, especially for the mining community, including increasing people's income, opening up employment opportunities, and increasing community creativity. In addition, to overcome the impacts that arise, mining managers must act proactively and be responsible for their activities. However, when compared, the negative impacts of mining often outweigh the positive impacts on surrounding communities. Therefore, the village government needs to emphasize sanctions against these activities for the good and welfare of the local community. Keywords: Sand mining, public welfare